The role of ecotourism in sustainable tourism development - Dailbor Redžić (Mенаџмент у хотелијерству и туризму, 2017)
Increased number of participants in international tourism in addition to a number of positive economic effects has certain negative implications that are associated with the factors that cause global warming. As inhabitants of the planet earth, we need to be responsible and have a moral obligation to protect and preserve the environment in which we live and travel, while promoting practices to minimize the impact of harmful gases into the atmosphere. The growth of environmental awareness with putting emphasis on the reduction of greenhouse gas emissions that contribute to ecotourism becomes a key driver for future tourism development. Ecotourism with the concepts of "green consumption" aims to protect the environment, increase the social responsibility of the participants in tourist travel and encourage economic development and environmental sustainability of natural areas. In this study, we will analyze modern concepts of sustainable and ecotourism tourism in order to emphasize the need to develop sustainable operations of business entities in tourism.